CLASSIFICATION OF SOCIAL PROTEST IN CONTEMPORARY JAPAN - D. V. Streltsov (Vestnik MGIMO-Universiteta)
The author makes an attempt to classify the political manifestations of social protest in postwar Japanese history. The author identifies five types of politically orchestrated social protest: ideological, socio-class, problem centered, conservative and local. The specificity of concrete forms of protest is analyzed from the points of view of their substance and organization. After the end of the cold war the ideological type of social protest which had earlier played the role of the ideological basis for the consolidation of the left opposition political forces, loses its initial driving force. The aggravating crisis of the traditional corporate model decreases the significance of the social-class protest which had been an instrument of pressure over state power in favor of an active policy in the social sphere/ Also diminishing in the present-day Japan is the conservative protest as a public dissent against the ruling party caused by weakening of its ability to take into acount the interests of specific social minorities that had traditionally been prioritized by state support. Meanwhile the problem-centered and local types of protest are gaining more importance in today’s Japan as they rely on a relatively broad social support. For the opposition parties social protest is nothing more than an opportunity to attract additional votes. Lacking any real chance of coming to power, these parties use mass protest mood for the consolidation of their electoral base. Many voters, disillusioned with the ability of political parties to extrapolate their opinion on the sphere of public policy decision-making, become more and more inclined not to come to the polls at all.